Pregnancy and harmful radiations - Danesh Kajori M (Iran University of Medical Sciences, 1989)
Most women want to know about possible consequences radiology, radioisotope or even television terminal. Because knowing about them, prevent from fear. Fetus is inevitably placed to some types of radiation. Environmental radiation occurs from atmosphere, soil and buildings. Total radiation above, ingested and possibly inhaled radioisotopes probably is seventy five-thousandth to one-tenth of RAM in pregnancy.   So pregnant women who worked with radioactive isotopes will be asked to limit working hours until the amount of radiation received by fetus not more than half RAM. The amounts of radiation are intake in abdominal radiography is approximately 1 or more than 1 RAM.